Insight on Diagnosis and Treatment From Over a Decade of Research Through the University of Chicago Monogenic Diabetes Registry - Bowden, Tiana L.; Letourneau-Freiberg, Lisa R.; Kandasamy, Balamurugan; Sanyoura, May; Tian, Persephone; Harris, Anastasia G.; Bell, Graeme I.; Philipson, Louis H.; Naylor, Rochelle N.; Greeley, Siri Atma W. (Frontiers in Clinical Diabetes and Healthcare, 2021)
Monogenic diabetes is a category of diabetes mellitus caused by a single gene mutation or chromosomal abnormality, usually sub-classified as either neonatal diabetes or maturity-onset diabetes of the young (MODY). Although monogenic diabetes affects up to 3.5% of all patients with diabetes diagnosed before age 30, misdiagnosis or improper treatment occurs frequently. The University of Chicago Monogenic Diabetes Registry, established in 2008, offers insight into the diagnosis, treatment, and natural history of individuals known or suspected to have monogenic diabetes. Those interested in participating in the Registry begin by completing a secure web-based registration form. Participants are then screened for eligibility and consented either by phone, video call, or in person. Relevant medical and family history is collected at baseline and then annually via surveys through our secure REDCap database. The University of Chicago Monogenic Diabetes Registry has enrolled over 3800 participants from over 2000 families. To date, over 1100 participants have a known genetic cause of diabetes. While many Registry participants reported being referred through their diabetes care provider (54%), a large portion also learned about the Registry through web searching (24%), friends/family (18%), or other sources (13%). Around two-thirds of those with a known genetic cause had research-based genetic testing completed rather than clinical testing due to insurance coverage difficulties. Of those who were found to have monogenic diabetes, significant delays in diagnosis were identified, which highlights the need for increased access to clinical testing covered by insurance companies. GCK mutations were the most common cause of MODY (59%) followed by HNF1A mutations (28%), while mutations in KCNJ11 were the most common form of neonatal diabetes (35%) followed by INS (16%). Over the last decade, improvements in data collection for the University of Chicago Monogenic Diabetes Registry have resulted in increased knowledge of the natural history of monogenic diabetes, as well as a better understanding of the most effective treatments. The University of Chicago Monogenic Diabetes Registry serves as a valuable resource that will continue to provide evidence to support improved clinical care and patient outcomes in monogenic diabetes.